Sorte versus habilidade, uma abordagem através de cross section da indústria de fundos de ações no Brasil - Bahia, Diogo Alexandre de Melo (2012)
Initially, we test the hypothesis that actively managed funds presents alphas (excess return) when compared to the Brazilian equity indexes used by passive funds. Then bootstrap simulations check if theses alphas can be attributed just to luck. Using this methodology we find that the aggregate portfolio of actively managed Brazilian equity funds has not presented excess of return from the two most important equity indexes in Brazil (true alpha), returns considered after cost and expenses. Bootstrap simulations suggests that a greater number of funds produces better returns adjusted to benchmark than we would expect just because of randomness in the returns.